2014
DOI: 10.17795/ajmb-18611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Skin Penetration Enhancers in Topical Antiaging Products Containing α-HydroxyAcids and Hyaluronic Acid

Abstract: Background: Transdermal drug delivery has several advantages and has been vastly investigated over the last decades. Chemical enhancers improve the quantity of drug penetration through the skin. Objectives: In this study, some conventional solvents and surfactants were used as enhancers to promote dermal penetration of α-hydroxyacids (AHA) and hyaluronic acid (HA). Materials and Methods: A total of 42 different formulations containing AHA or HA as the active ingredient and a solvent or surfactant as the enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Since penetration of albumin into skin is very poor, it needs enhancers to permeate the skin efficiently. Because albumin is a hydrophilic high MW molecule[ 12 34 ] hindering it to pass the skin. The profile of albumin skin permeation showed its maximum after 1 h, which was 5±0.5 mg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since penetration of albumin into skin is very poor, it needs enhancers to permeate the skin efficiently. Because albumin is a hydrophilic high MW molecule[ 12 34 ] hindering it to pass the skin. The profile of albumin skin permeation showed its maximum after 1 h, which was 5±0.5 mg.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that albumin which is non permeable through skin was able to cross the skin when administered CaP-NPs[ 13 ]. We have previously proved that CPEs were effective for enhancing the skin permeation of albumin and other proteins[ 33 34 ]. In this work, we studied effects, process and differences of CaP-NPs and ZnO-NPs in enhancing the skin permeation of albumin.…”
mentioning
confidence: 99%
“…show higher permeation and lower skin deposition than formulation without paraffins {F2}. This can be refered to that paraffins have permeation promoter effect [33]. In the paper reported by Ammar et al, skin deposition value of the chosen formulation was 28.85 % after 6 h experiment and permeation value of 36.4 % after 6 h.…”
Section: In Vitro Drug Releasementioning
confidence: 94%
“…Chemical penetration enhancers (CPEs) should build blocks to make new skin microstructures without 3 irritation . CPEs include aliphatic acids, fatty acids, 1,8,9 esters, alcohols, oils, terpens and etc. .…”
Section: Review Articlementioning
confidence: 99%